Inflammasome Activation in Pulmonary Arterial Hypertension - Foley, Anna; Steinberg, Benjamin E.; Goldenberg, Neil M. (Frontiers in Medicine, 2022)
Inflammasomes are multi-protein complexes that sense both infectious and sterile inflammatory stimuli, launching a cascade of responses to propagate danger signaling throughout an affected tissue. Recent studies have implicated inflammasome activation in a variety of pulmonary diseases, including pulmonary arterial hypertension (PAH). Indeed, the end-products of inflammasome activation, including interleukin (IL)-1β, IL-18, and lytic cell death (“pyroptosis”) are all key biomarkers of PAH, and are potentially therapeutic targets for human disease. This review summarizes current knowledge of inflammasome activation in immune and vascular cells of the lung, with a focus on the role of these pathways in the pathogenesis of PAH. Special emphasis is placed on areas of potential drug development focused on inhibition of inflammasomes and their downstream effectors.